OCCLUSAL PLANE EVALUATION IN DENTATE PATIENTS FOR COMPLETE DENTURE PROSTHODONTIC PRACTICE - Raza, Muhammad; Ayub, Nuzhat; Imran, Mehreen; Nawaz, Khurram; Sami, Asma (Journal of Ayub Medical College Abbottabad, 2020)
Background: Preclinical determination of occlusal plane is an important clinical step in construction of complete denture. Objective of present study was to find out the parallelism of occlusal plane to ala-tragus line in dentate subjects to provide a guideline for establishment of occlusal plane for edentulous patients Methods: In local dental College from April to October 2017 using purposive sampling technique this comparative study was conducted. After preliminarily examination, desired photographs of 120 subjects using fulfilling the inclusion criteria were taken biting on proper positioned Fox’s Plan. Photographs were analysed through the computer software named Digimizer Image Analysis (Version 4.2.5.0) for three posterior reference points on the tragus of the ear at its superior (ATs), middle (ATm) and inferior (ATi) margin and one anterior reference point, i.e., Inferior margin of the Ala of the nose. Three lines were drawn with the help of the software that were extending from the posterior reference points to anterior reference point and fourth line Parallel to the upper level of the fox plane (FxP). Finally, the angles between the above-mentioned lines computed were analysed to check the parallelism. One sample T- test was utilized using SPSS. Results: Mean angles value on right side of subjects between FxP to three reference points ATs, ATm, ATi were 3.261, 2.720 and 2.245 and on the left they were 2.347, 2.558 and 2.029 respectively showing no parallelism (angle value zero). Conclusion: Major findings revealed no parallelism among these planes. Keywords: occlusion; plane; denture